Into the Land of Wonder: The Narrative Life of Dying Neural Cells in Dementia Stories (Altre Modernità, 2024)
This paper aims at engaging in dialogue with diverse perspectives on neuropathology by examining the intersections between biopsychiatric and narrative portrayals of dementia. Firstly, we investigate how neurocognitive disorder is depicted in narrative form (in prose and verse), emphasising the significance of “narrative brain scans” as sites of intersubjective exploration of this complex experience. Secondly, we emphasise the unique potential of dementia narratives in prompting contemplation of whether the disruption of consciousness can be questioned through imagination and storytelling. Ultimately, narratives of dementia serve to practice wonder and not knowing (Candiani), and challenge reductionist boundaries between life and death, presence and absence of consciousness. Employing Lewis Carroll’s Alice’s Adventures in Wonderland (1865) as a narrative framework, this paper embarks on a journey in search of wonder within narratives by Mariangela Gualtieri, Jonathan Franzen, and John Bayley, depicting progressive cognitive decline.